Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4049/jimmunol.178.4.2241
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoplasmic Reticulum-Associated Aminopeptidase 1 in Immunity to Infection and in Cross-Presentation

Abstract: Endoplasmic reticulum-associated aminopeptidase 1 (ERAP1) is involved in the final processing of endogenous peptides presented by MHC class I molecules to CTLs. We generated ERAP1-deficient mice and analyzed cytotoxic responses upon infection with three viruses, including lymphocytic choriomeningitis virus, which causes vigorous T cell activation and is controlled by CTLs. Despite pronounced effects on the presentation of selected epitopes, the in vivo cytotoxic response was altered for only one of several epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
85
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 39 publications
9
85
0
6
Order By: Relevance
“…While further studies utilizing antigenpresentation assays in the presence or absence of biochemical inhibitors will enable deciphering these mechanisms, the use of MD as an OVA-delivery vehicle indeed reduces the threshold of OVA concentration required for effective cross-presentation by BMDC. This observation is consistent with previous studies, in which high concentrations of soluble OVA have been used to induce cross-presentation [31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…While further studies utilizing antigenpresentation assays in the presence or absence of biochemical inhibitors will enable deciphering these mechanisms, the use of MD as an OVA-delivery vehicle indeed reduces the threshold of OVA concentration required for effective cross-presentation by BMDC. This observation is consistent with previous studies, in which high concentrations of soluble OVA have been used to induce cross-presentation [31][32][33].…”
Section: Discussionsupporting
confidence: 93%
“…The increase in GSW11 generation occurred despite an overall decrease in MHC I levels; MHC I downregulation is typically observed in ERAAP-knockout cells (Fig. 1D) (11)(12)(13)(14). This confirmed that the generation of GSW11 is ERAAP sensitive.…”
Section: Resultssupporting
confidence: 68%
“…In humans, two aminopeptidases perform this function, ERAP1 and ERAP2 (7)(8)(9); in mice, only one aminopeptidase exists, ERAAP (10). ERAAP is critical for the generation of many antigenic epitopes in vivo and can influence the generation of the antigenic peptide repertoire (11)(12)(13)(14). ERAAP can also destroy antigenic epitopes by trimming them to lengths too small for MHC binding, thus its characterization as an antigenic peptide editor (12).…”
mentioning
confidence: 99%
“…As identifying antigenic peptides is difficult in the clinical setting, these double Tg mice (i.e., B27/ERAP Studies with ERAP-deficient mice have shown reduced cell surface expression of MHC I molecules, but not MHC II (10,11). These mice show no differences in the profile of CD4 and CD8 compared with mice with intact ERAP.…”
Section: /2mentioning
confidence: 99%